A descriptive study of the bullet journal as a personal informatics system - Tan, Beatrice Bernardin G.; Olgado, Benedict S. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2021)
This study looks at bullet journaling as a personal informatics practice. It argues that bullet journaling echoes and expands the stages of personal informatics systems. Interviews with 10 long-term bullet journalists identify the motivations, categories of information, and actions surrounding the practice. Organization, productivity, and introspection motivates participants into starting a bullet journal. They create self-trackers concerned with their habits, health, hobbies, and housekeeping. Selection, design, and utilization constitute the three stages of bullet journaling. The findings show that bullet journaling addresses the barriers of personal informatics through its customizability, flexibility, and creativity. Additionally, bullet journaling provides a semblance of the personal informatics experience because its three main stages are largely similar to the stages of personal informatics systems with the exception of the design stage. However, bullet journaling is not an infallible practice because its affordances can become constraints for long-term users. Further studies should account for the experiences of new bullet journalists as well as old bullet journalists who abandoned the practice.
Thesis
Keywords: Personal information management; Time management